2013
DOI: 10.1017/s1461145712000429
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of the mood stabilizer lamotrigine against glutamate excitotoxicity: roles of chromatin remodelling and Bcl-2 induction

Abstract: Lamotrigine (LTG), a phenyltriazine derivative and anti-epileptic drug, has emerged as an effective first-line treatment for bipolar mood disorder. Like the other mood stabilizers lithium and valproate, LTG also has neuroprotective properties but its exact mechanisms remain poorly defined. The present study utilized rat cerebellar granule cells (CGCs) to examine the neuroprotective effects of LTG against glutamate-induced excitotoxicity and to investigate potential underlying mechanisms. CGCs pretreated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 68 publications
(87 reference statements)
3
29
0
Order By: Relevance
“…Lithium, valproate and lamotrigine are enhancers of neurogenesis (Manji et al, 2000;Leng et al, 2013) and are also investigated in various models of Table 3 Effect of chronic treatment with perampanel on the number of c-Fos proteinpositive cells/0.1 mm 2 in different brain regions of Gria1 À / À and WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium, valproate and lamotrigine are enhancers of neurogenesis (Manji et al, 2000;Leng et al, 2013) and are also investigated in various models of Table 3 Effect of chronic treatment with perampanel on the number of c-Fos proteinpositive cells/0.1 mm 2 in different brain regions of Gria1 À / À and WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, lithium administration was able to disrupt rotenone's epigenetic actions without affecting DNMT and TET activity [65]. Another study showed that lamotrigine protected neurons against excitoxicity in rat cerebellar granule cells [67]. This action was hypothesized to be mediated by a moderate increase in histone acetylation.…”
Section: Epigenetic Effects Of Mood Stabilizers In Animalsmentioning
confidence: 99%
“…This hypothesis was further supported by a slight attenuation of HDAC caused by lamotrigine. The antiapoptotic effects of lamotrigine seemed to result from increased acetylation of B-Cell CLL/Lymphoma 2 (bcl-2) promoter and subsequent upregulation [67]. As far as VPA is concerned, neuroprotective actions were accompanied by H3 hyperacetylation in a series of induced-neurotoxicity cell models [57,[68][69][70].…”
Section: Epigenetic Effects Of Mood Stabilizers In Animalsmentioning
confidence: 99%
“…Likewise, identification of VPA as a class I and IIa HDAC inhibitor (Gottlicher et al, 2001;Phiel et al, 2001) suggests that associated reversion of HDACdependent transcriptional rep ression and histone hyperacetylation could be involved in its mood-stabilizing properties (Gavin and Sharma, 2010;Machado-Vieira et al, 2011). Less studied are the mechanisms of action of LTG and CBZ; neuroprotective effects of LTG exerted through upregulation of excitatory amino acid transporter activity (Schloesser et al, 2012;Leng et al, 2013) and increased global DNA methylation induced by CBZ (Pisanu et al, 2018) are the best described epigenetic changes. The histone deacetylase inhibitory properties of anticonvulsants (Eyal et al, 2004) and the potent antioxidant effects of lithium (Leng et al, 2008;Dwivedi and Zhang, 2015) have been postulated as potential pathways to reverse dysfunctional epigenetic regulation and variability in treatment response (Machado-Vieira et al, 2011).…”
Section: Introduction Rationalementioning
confidence: 99%